2017
DOI: 10.1155/2017/6029075
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Reduce Postoperative Infections in Patients Undergoing Colorectal Surgery: A Systematic Review and Meta-Analysis

Abstract: Background. We performed this meta-analysis to investigate the efficacy of probiotics on prevention of infection-related complications following colorectal resection. Method. PubMed, EMBASE, Cochrane Library, and the Web of Science were searched up to January 2016. According to the results, only randomized controlled trials that compared the efficacy of probiotics on patients with colorectal resection were included for meta-analysis. Results. Nine studies including a total of 1146 patients met the criteria (55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…ere are clinical trials that prove efficacy of oral probiotics for various skin problems [22,55] and even for lowering the rate of surgical site infections [56][57][58]. A recent meta-analysis [59] has also concluded that a reduction of surgical site infections following colorectal surgery was found for patients that were administered probiotics. e reported mechanisms mainly included immune modulation including: increase of production of TNF-α and IL-10 [59], systemic cellular immune response [56], modulation of the gene expression of SOCS3 [58], and pathogen inhibition [59].…”
Section: Probiotics As Alternatives To Antibiotics For Woundmentioning
confidence: 99%
“…ere are clinical trials that prove efficacy of oral probiotics for various skin problems [22,55] and even for lowering the rate of surgical site infections [56][57][58]. A recent meta-analysis [59] has also concluded that a reduction of surgical site infections following colorectal surgery was found for patients that were administered probiotics. e reported mechanisms mainly included immune modulation including: increase of production of TNF-α and IL-10 [59], systemic cellular immune response [56], modulation of the gene expression of SOCS3 [58], and pathogen inhibition [59].…”
Section: Probiotics As Alternatives To Antibiotics For Woundmentioning
confidence: 99%
“…Liu et al in another study (2015) concluded that probiotics reduced postoperative infections in patients with liver metastasis 20 . Three systematic reviews (2017) and one metaanalysis (2015) also confirmed the protective effects of probiotics and synbiotics consumption before ab-dominal surgery, which reduced infective complications such as urinary tract infections, pneumonia and sepsis 15,[20][21][22][23][24] . Liu et al recommended a diet that included bacteria of different strains, and this diet was more useful than single-strain diets for surgical infections and other infections 22 .…”
Section: Discussionmentioning
confidence: 88%
“…Probiotics can be used to support the restoration of a healthy gut microbiota in patients undergoing surgical procedures. The formulation of probiotics and their efficacy for use with patients undergoing colorectal resection was evaluated in a recent systematic review of over 1000 patients (Liu et al, 2017). The authors concluded that a combination of multistrain probiotics was associated with a reduction in total number of infections (OR=0.30, 95%CI: 0.15-0.61, p=0.0009), including surgicalsite infections (OR=0.48, 95%CI: 0.25-0.89, p=0.02) and nonsurgical-site infections (OR=0.36, 95%CI: 0.23-0.56, p<0.00001), while there was no significant reduction when single-strain or dualstrain probiotics were used (OR=0.74, 95%CI: 0.50-1.09, p=0.13) (Liu et al, 2017).…”
Section: Surgical Infectionsmentioning
confidence: 99%
“…The formulation of probiotics and their efficacy for use with patients undergoing colorectal resection was evaluated in a recent systematic review of over 1000 patients (Liu et al, 2017). The authors concluded that a combination of multistrain probiotics was associated with a reduction in total number of infections (OR=0.30, 95%CI: 0.15-0.61, p=0.0009), including surgicalsite infections (OR=0.48, 95%CI: 0.25-0.89, p=0.02) and nonsurgical-site infections (OR=0.36, 95%CI: 0.23-0.56, p<0.00001), while there was no significant reduction when single-strain or dualstrain probiotics were used (OR=0.74, 95%CI: 0.50-1.09, p=0.13) (Liu et al, 2017). Studies also suggest that perioperative use of probiotics or synbiotics (probiotics mixed with a non-digestive food ingredient that stimulates bacterial growth, known as prebiotics) in patients undergoing What differences are there between using probiotics in paediatric and adult patients?…”
Section: Surgical Infectionsmentioning
confidence: 99%